2018
DOI: 10.31577/sociologia.2018.50.4.18
|View full text |Cite
|
Sign up to set email alerts
|

Negative Aspects of Municipal Amalgamation within the Municipal Reform – the Perspective on the Example of the Slovak Republic

Abstract: Katedra humánnej geografie a demografie, PriF UK, Bratislava Sales House SK s.r.o., Bratislava Negative Aspects of Municipal Amalgamation within the Municipal Reformthe Perspective on the Example of the Slovak Republic. The issue of municipal reform is clearly one of the major topics related to whole society. Many authors agree with its n ecessity, but their views of further direction of municipal reform diverge. On one hand there are preferences of maintaining the current model of cooperation with the legisla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The last column of the table in Appendix C reports this classification. Although this typology is heavily used and respected (Andráško and Ira, 2010 ; Huba et al 2010 ; Bleha, 2011 ; Jaszczak et al 2018 ; Klobučník et al 2018 ), it produces classifications that are not very compliant with the present viability assessment of municipalities. The optimal scaling procedure of Young ( 1981 ) employed to transform the ordinal scale of the categories introduced by Gajdoš et al ( 2009 ) into continuous measurements identified that the correlation may vary between 0.229 and −0.783.…”
Section: Resultsmentioning
confidence: 99%
“…The last column of the table in Appendix C reports this classification. Although this typology is heavily used and respected (Andráško and Ira, 2010 ; Huba et al 2010 ; Bleha, 2011 ; Jaszczak et al 2018 ; Klobučník et al 2018 ), it produces classifications that are not very compliant with the present viability assessment of municipalities. The optimal scaling procedure of Young ( 1981 ) employed to transform the ordinal scale of the categories introduced by Gajdoš et al ( 2009 ) into continuous measurements identified that the correlation may vary between 0.229 and −0.783.…”
Section: Resultsmentioning
confidence: 99%
“…Fragmentation of the settlement structure [6], which is associated with a very large variability in the size of municipalities in Slovakia [12], can be solved by merging municipalities or inter-municipal cooperation [8]. Forms of inter-municipal cooperation are a natural part of the functioning of self-governments, which aim is to more effectively secure the competencies of municipalities in different areas of everyday life [3].…”
Section: Introductionmentioning
confidence: 99%